2021
DOI: 10.1080/23311908.2021.1886626
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression and health risk behaviors among university students, Karachi, Pakistan

Abstract: In our society, people's health behaviors are considered a dilemma that can intensify the probability of developing a disease in the future. This study aimed to investigate the association between health risk behaviors and depression among a sample of university students, Karachi, Pakistan. A self-reported health behavior questionnaire was distributed to 813 consented students. The Center for Epidemiological Studies-Depression (CES-D-10) questionnaire was used, a short, self-report scale that measures the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(42 reference statements)
0
3
1
Order By: Relevance
“…On the other hand, a Pakistani study reported a much higher prevalence of depression symptoms (71%) and anxiety symptoms (72%) among medical students [43] . In contrast to our results, a previous report indicated that 12.5% of depression prevalent among university students [44] . In some developed countries, a low prevalence of depression, anxiety, and distress symptoms was reported [15] .…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, a Pakistani study reported a much higher prevalence of depression symptoms (71%) and anxiety symptoms (72%) among medical students [43] . In contrast to our results, a previous report indicated that 12.5% of depression prevalent among university students [44] . In some developed countries, a low prevalence of depression, anxiety, and distress symptoms was reported [15] .…”
Section: Discussioncontrasting
confidence: 99%
“…The gender-related findings align with existing literature. Rehman et al (2021) observed that in a sample of university students in Karachi, females exhibited a 70% higher prevalence of depression compared to males. Similarly, another study examining stress and depression rates among university students in Karachi, found significant gender differences, with female students displaying higher levels of depression than their male counterparts (Naseem et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In another study within the Pakistani context, (Asif et al, 2020) discovered that among a sample of 500 undergraduate students, 75% reported varying levels of depression, ranging from mild to extremely severe, and 88.4% reported similar levels of anxiety. Rehman et al (2021) also reported that 12.5% of the 813 university students surveyed in Karachi had depression, which was associated with factors such as social isolation, dissatisfaction with life, and insomnia.…”
mentioning
confidence: 99%
“…Approximately 25% of the total world population and about 34% of people in Pakistan endure agony due to this disorder. 3 It is usually exhibited as mild, moderate and severe levels. 4 Depression is explained as an emotional condition with feelings of sadness, hopelessness, low self-esteem or guilt, disturbance in sleep and appetite, and no interest in different activities.…”
Section: Introductionmentioning
confidence: 99%